A Case of Macrolide-Refractory Mycoplasma pneumoniae Pneumonia in Pregnancy Treated with Garenoxacin. (10th December 2017) - Matsuda, Yoko; Chigusa, Yoshitsugu; Kondoh, Eiji; Ito, Isao; Ueda, Yusuke; Mandai, Masaki
Abstract : Pneumonia in pregnancy is associated with adverse maternal and foetal outcomes, and intensive treatment with appropriate antibiotics is essential. However, cases caused by pathogens that are resistant to antibiotics suitable for the developing foetus are challenging. We herein report a case of macrolide-refractory Mycoplasma pneumoniae pneumonia in pregnancy. A 40-year-old multigravida with twin pregnancy complained of cough and fever at 13 weeks of gestation and was diagnosed with pneumonia. Even though empiric treatment with ceftriaxone and oral azithromycin was started, her condition deteriorated rapidly. The findings of chest computed tomography suggested Mycoplasma pneumoniae pneumonia. Since azithromycin did not work, this strain was considered to be macrolide-refractory. Garenoxacin, an oral quinolone, was selected and was dramatically effective. The use of quinolone could be justified with the emergence of drug-resistant bacterial/atypical pneumonia and in the maternal life-threatening condition.